In vivo horizontal dissemination of the blaKPC-2 gene carried on diverse genetic platforms among clinical isolates of Enterobacteriaceae. Issue 3 (September 2015) - Anchordoqui, M.S.; De Belder, D.; Lucero, C.; Rapoport, M.; Faccone, D.; Rodriguez, A.; Di Martino, A.; Martino, F.; Herrero, I.; Pasteran, F.; Corso, A.; Gomez, S.A.
Highlights: We describe three cases of intrapatient transfer of bla KPC-2 between Enterobacteriaceae. In each case, bla KPC-2 was harboured in different genetic platforms and plasmids. One of the platforms detected is a novel variant of the Tn 3 -derived transposon. This work describes the variety of genetic elements harbouring bla KPC that are circulating in Argentina. This is the first report of E. coli harbouring bla KPC in Tn 4401a in Argentina. Abstract: This study investigated the molecular characteristics of six bla KPC -positive Enterobacteriaceae recovered from three patients in Argentina. Antimicrobial susceptibility testing was performed following Clinical and Laboratory Standards Institute (CLSI) 2014 recommendations. Molecular characterisation of the isolates was performed by biparental conjugation, PCR, sequencing, S1 nuclease restriction, and Southern blot hybridisation with a bla KPC probe using standard protocols and conditions. The isolates studied were as follows. Case 1: Escherichia coli (ECO-P1) and Klebsiella pneumoniae (KPN-P1) isolated from a rectal swab harboured bla KPC-2 in transposon Tn 4401a on non-typeable and non-conjugative plasmids. Case 2: Enterobacter cloacae (ECL-P2) and K. pneumoniae (KPN-P2) were isolated from two blood cultures. bla KPC-2 was found in a novel genetic variant of IS Kpn8 – bla KPC-2 –IS Kpn6 -like on conjugative plasmids of IncL/M type. Case 3, Citrobacter freundii (CFR-P3) and Klebsiella oxytoca (KOX-P3) were isolated from skin and skin-structure infection. The bla KPC gene was detected on IS Kpn 8–Δ bla TEM – bla KPC-2 –IS Kpn6 -like located on an IncA/C conjugative plasmid. CFR-P3 and KOX-P3 harboured bla PER-2 in addition to the bla KPC gene. In conclusion, we document the horizontal dissemination of bla KPC-2 from diverse Enterobacteriaceae clinical isolates with different genetic backgrounds. This is the first report of E. coli harbouring bla KPC associated with Tn 4401a in Argentina.